Acid-fast bacteria as causative agents of skin and soft tissue infections: case presentations and literature review - Spiliopoulou, Anastasia; Kyriakou, Georgia; Georgiou, Sophia; Lekkou, Alexandra; Leonidou, Lydia; Militsopoulou, Maria; Papadogeorgaki, Eleni; Christofidou, Myrto; Kolonitsiou, Fevronia; Paliogianni, Fotini (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
Acid-fast bacteria can be implicated in skin and soft tissue infections. Diagnostic identification can be challenging or not feasible by routine laboratory techniques, especially if there is no access to the Matrix Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry (MALDI-TOF MS) technology. Here, we present two cases of skin and soft tissue infections caused by two different acid-fast bacteria, Nocardia brasiliensis and Mycobacterium marinum. They both grew on Löwenstein–Jensen medium, Sabouraud agar medium and blood agar medium. Both bacteria appeared acid-fast by Ziehl–Neelsen stain and Gram-positive by Gram stain. The identification was performed by MALDI-TOF MS and gene analysis. N. brasiliensis and nontuberculous mycobacterium M. marinum represent rare pathogens that cause severe skin and soft tissue infections. Failure to identify the causative agent and subsequent inappropriate or inadequate treatment may lead to severe complications or even disseminated disease, especially in immunocompromised individuals.